Integrated Marketing Communication: The Rinra Makassar Hotel Increases Occupancy - Yulhaidir Yulhaidir; Risca Pratisca (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
The purpose of this study was to determine the integrated marketing communication carried out by The Rinra Makassar hotel as an effort to increase occupancy. This type of research uses a qualitative descriptive method. Data obtained by interviewing the Director of Sales Marketing, Ass. Marcomm Manager, and Sales Executive as well as making observations. The results of this study indicate that the Integrated Marketing communication carried out by The Rinra Makassar hotel as an effort to increase occupancy, namely the promotion mix includes advertising (advertising), public relations (public relations), personal selling (personal sales), sales promotion (sales promotion). , and direct marketing (direct marketing). This is proven as a factor in the increase in occupancy at The Rinra Makassar hotel.